THE INFLUENCE OF SERVICE QUALITY AND MENU DIVERSITY ON PURCHASING DECISIONS AT CAFÉ SOCOLATTE PIDIE JAYA DISTRICT - Erni Zahara; Agustinawati; Siti Maimunah; T. Edyansyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The purpose of this study was to determine and analyze the effect of service quality (Physical Evidence, Reliability, Responsiveness, Assurance, Empathy) and menu diversity on purchasing decisions at Café Socolatte, Pidie Jaya Regency. The data analysis technique used is multiple linear regression analysis using the SPSS program. The results showed that simultaneously service quality and menu diversity had a positive and significant effect on purchasing decisions at Café Socolatte, Pidie Jaya Regency. Partially, service quality, physical evidence of reliability, responsiveness, assurance, empathy and menu diversity have a positive and significant effect on purchasing decisions at Café Socolatte, Pidie Jaya Regency.